Long-run inflation-unemployment dynamics: The Spanish Phillips curve and economic policy - Marika Karanassou; Héctor Sala; Dennis J. Snower (Centre for Economic Policy Research (CEPR), 2003)
This Paper takes a new look at the long-run dynamics of inflation and unemployment in response to permanent changes in the growth rate of the money supply. We examine the Phillips curve from the perspective of what we call `frictional growth', i.e. the interaction between money growth and nominal frictions. After presenting theoretical models of this phenomenon, we construct an empirical model of the Spanish economy and, in this context, we evaluate the long-run inflation-unemployment trade-off for Spain and examine how recent policy changes have affected it.
Keywords: E20; E30; E40; E50; J30; 330; Phillips-Kurve; Geldmengensteuerung; Spanien